Grenzen der Völkerrechtsfreundlichkeit - Abend, Theresa (Universitätsverlag Göttingen, 2019)
In the view of the increasingly strong and far-reaching international interdependence of the national legal system, the question as to where the German Basic Law relates concerning the increasing international complexity is becoming ever more important. In response to this, the German Basic Law is said to be a constitution open to international law, which is extracted from the basic principle of 'Völkerrechtsfreundlichkeit' (friendliness toward international law). However, it remains vague in which relation such a principle would stand to the rule of law, the principle of democracy or the system of basic rights, if it is inserted into their limitations or constitutes a supreme premise. The focus of this study lays upon the attempt to make the principle of Völkerrechtsfreundlichkeit tangible and to explore its legal content of.